The differing relationships between academic discipline, sleep hygiene, and dysfunctional sleep attitudes on sleep quality and duration in Canadian university students - Kuhn, Tara; Karsan, Sameena; Heisz, Jennifer J.; Middleton, Laura E. (Frontiers in Psychology, 2024)
Objectives This study sought to understand how university student’s academic discipline relates to sleep factors including attitudes, hygiene, quality, and duration. Methods Using a cross-sectional approach, a 30-min survey was advertised to students at two Canadian universities in March of 2022. Sleep measures included the Dysfunctional Beliefs and Attitudes Scale, the Sleep Hygiene Index, the Pittsburgh Sleep Quality Index, and the Insomnia Severity Index. Academic discipline was categorized into four groups: Health, Arts, Sciences, and Engineering. Multiple linear regressions were used to investigate (1) the effect of academic discipline on sleep measures, and (2) the effect of academic discipline, dysfunctional sleep attitudes, and sleep hygiene practices on insomnia, sleep quality and duration. Results 1,566 students completed the survey (69.4% women; 80.3% undergraduates). Compared to Health students, Art students had worse dysfunctional sleep attitudes, hygiene, quality, and insomnia severity (p < 0.001). This relationship disappeared after controlling for differences in mental health (p ≥ 0.05). Art students had longer sleep durations (p < 0.01), whereas Engineering students had shorter sleep durations (p < 0.05). When dysfunctional sleep attitudes and hygiene were included in the model, both academic discipline (p < 0.05) and sleep hygiene (p < 0.001) were associated with sleep duration. Sleep hygiene and attitudes were also associated with sleep quality and insomnia severity (p < 0.001), while academic discipline was not (p ≥ 0.05). Discussion These results suggest differences in sleep quality across academic discipline are impacted by dysfunctional sleep attitudes, sleep hygiene, and mental health, whereas differences in sleep duration appear to be independent of these factors. Overall, students in different academic disciplines have unique relationships with sleep and thus may require targeted approaches to improve their sleep. Future interventions should focus on supporting sleep hygiene and attitudes to improve students’ sleep and well-being.